Study of the competitiveness of industrial parks using conjoint analysis - Iryna Kohut; Tetyana Lebid; Solomiia Fedushko; Iryna Klymchuk (Research in Globalization, 2023)
In an environment of high competition, globalization, war and certain restrictions of the World Trade Organi zation, Ukraine is forced to look for new ways to revive its economy. Today, one of the tools for the future development of Ukraine's economy is the creation, development and operation of industrial parks. The article analyzes the market of industrial parks in Ukraine: current state and development prospects. Using the PESTEL analysis, the author studies the factors influencing the strength of competition in this area. The analysis of scientific sources and the results of the authors' research suggests that the level of competitiveness of industrial parks in Ukraine depends on the rental price of office and production space, the cost of labor in the region, the level of infrastructure development, the developer's image and the distance to the border with the EU countries. Conjoint analysis is a popular and reliable statistical method for studying the preferences of future consumers of a product or service. With this tool's help, the article deter-mines the importance of factors that affect the competitiveness of industrial parks in Ukraine. It should be noted that this method also makes it possible to assess the level of competitiveness at given values of each factor, which will allow concentrating the efforts and re sources of the en-terprise (industrial park) on increasing the level of the most important ones.
Keywords: 330; Conjoint analysis; PESTEL analysis; Industrial parks; Economic development; Competitiveness; Environment; Investments